Case report: Successful treatment of acute generalized pustular psoriasis with multiple comorbidities with oral tacrolimus - Zhao, Mingdan; Huang, Fujun; Tang, Lei; Zhou, Xun; Zhang, Miao; Liao, Mengxue; Liu, Lirong; Huang, Mengya (Frontiers in Immunology, 2024)
Acute generalized pustular psoriasis (GPP) is a serious illness. Despite various treatment methods, there is still lack of effective treatment plans for refractory cases with multiple comorbidities. This case report presents a 67-year-old woman with acute GPP, stage 4 chronic kidney disease (CKD), type 2 diabetes, and cardiovascular disease, in whom skin symptom disappearance and kidney function improvement were observed after the use of oral tacrolimus as the sole therapy. This is the first report on the application of tacrolimus in the treatment of acute GPP, especially refractory acute GPP. The successful treatment indicates that there are shared immune pathways between acute GPP and CKD, and the pathways can be interdicted by tacrolimus. Further studies are needed to optimize the therapy to maximize efficacy and minimize toxicity.